2021
DOI: 10.1007/s12264-021-00800-x
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Cingulate Cortex Mediates Hyperalgesia and Anxiety Induced by Chronic Pancreatitis in Rats

Abstract: Central sensitization is essential in maintaining chronic pain induced by chronic pancreatitis (CP), but cortical modulation of painful CP remains elusive. Here, we examined the role of the anterior cingulate cortex (ACC) in the pathogenesis of abdominal hyperalgesia in a rat model of CP induced by intraductal administration of trinitrobenzene sulfonic acid (TNBS). TNBS treatment resulted in long-term abdominal hyperalgesia and anxiety in rats. Morphological data indicated that painful CP induced a significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 69 publications
2
18
0
Order By: Relevance
“…ACC is mainly related to selfconcentration of attention, self-regulation of emotion, and situational memory extraction (Alexander et al, 2021;Scotti-Muzzi et al, 2021). Previous study has reported that ACC was involved in anxiety disorder caused by physiological diseases (Chaibi et al, 2021;Ren et al, 2021). Our study consistently found that the increased ReHo values in PD-A patients were positively correlated with the HAMA scores, suggesting that alteration of ReHo in ACC might cause the dysfunction of self-emotion and consciousness regulation in PD patients, and thus inducing anxiety symptoms.…”
Section: Discussionsupporting
confidence: 80%
“…ACC is mainly related to selfconcentration of attention, self-regulation of emotion, and situational memory extraction (Alexander et al, 2021;Scotti-Muzzi et al, 2021). Previous study has reported that ACC was involved in anxiety disorder caused by physiological diseases (Chaibi et al, 2021;Ren et al, 2021). Our study consistently found that the increased ReHo values in PD-A patients were positively correlated with the HAMA scores, suggesting that alteration of ReHo in ACC might cause the dysfunction of self-emotion and consciousness regulation in PD patients, and thus inducing anxiety symptoms.…”
Section: Discussionsupporting
confidence: 80%
“…In this study, CP was induced by intraductal administration of trinitrobenzene sulfonic acid, and this model resulted in long-term abdominal hyperalgesia and anxiety in rats. Using chemogenetics, the authors found that specific inhibition of ACC pyramidal cells not only reduced the hyperalgesia but also alleviated anxiety, a major comorbidity of chronic pain in male Sprague-Dawley rats [6]. This study further supported an important role of the ACC in the regulation of pain and anxiety.…”
mentioning
confidence: 61%
“…Structural remodeling was detected in the ACC, manifested by an increase in dendritic spine density and the number of synapses in a rat model of CCI-induced pain, thereby mediating the occurrence of pain. Furthermore, recent research has found that the enhancement of neural remodeling in the ACC caused by injecting trinitrobenzenesulfonic acid into the pancreatic duct is involved in the development and maintenance of visceral pain sensitivity and anxiety in rats, which supports a strong link between ACC neuroplasticity and chronic pain [ 51 ]. In our present study, WB and IF staining both demonstrated that the expression levels of neuroplasticity-related proteins (MAP2, GAP43, and tau) decreased significantly.…”
Section: Discussionmentioning
confidence: 96%